2019
DOI: 10.4491/eer.2019.317
|View full text |Cite
|
Sign up to set email alerts
|

Screening and selection of autochthonous fungi from leachate contaminated-soil for bioremediation of different types of leachate

Abstract: This study aims to use contaminated soil with leachate to select autochthonous fungi that are able to bioremediate three types of leachate, (Young (YL), Intermediate (IL) and Old (OL)). Eleven fungal species were isolated via the enrichment method using the leachate as the sole source of carbon and energy. The isolates were evaluated for their ability to grow and remove organic pollutants at 100%, 50% and 25% (v/v) of leachate in both solid and liquid cultures that were spiked with malt extract. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Although toxic contaminants in leachate, including dissolved organic matter, heavy metals and organic xenobiotic compounds may have in uenced the microbial composition in the samples studied [51]. Our study is essential, since it was possible to observe a considerable microbial community related to pathogenic taxonomic groups, indicating care with potential leaks and environmental contamination.…”
Section: Microbial Community Functional Diversity and Bioremediation Potentialmentioning
confidence: 94%
“…Although toxic contaminants in leachate, including dissolved organic matter, heavy metals and organic xenobiotic compounds may have in uenced the microbial composition in the samples studied [51]. Our study is essential, since it was possible to observe a considerable microbial community related to pathogenic taxonomic groups, indicating care with potential leaks and environmental contamination.…”
Section: Microbial Community Functional Diversity and Bioremediation Potentialmentioning
confidence: 94%
“…The isolated fungi were identified following the atlases of mycology and previous The statistical analysis, Figure 3, shows 47% of the isolates from Soran City landfill sites belong to the genus of Aspergillus whose frequency was 72 and contained different species such as Aspergillus niger, Aspergillus fumigatus, Aspergillus terreus, Aspergillus flavus, Aspergillus pseudoelegans, and Aspergillus elegans, and 16% and 12% were species of Penicillium and Rhizopus whose frequencies were 25 and 19, respectively. Other studies have shown that aspergillus and penicillium were the dominating species in landfills (Zegzouti et al, 2020). The species of penicillium were divided into three different species.…”
Section: Isolation and Identification Of Fungimentioning
confidence: 97%
“…A suitable carrier can protect the microorganisms from the external environment as much as possible, and can also reduce the loss of microorganisms during immobilization. At present, the most widely used materials for immobilized microorganisms are divided into inorganic materials, natural organic polymer materials, synthetic organic polymer materials and composite materials [5][6].…”
Section: Materials For Immobilizing Microorganismsmentioning
confidence: 99%